A Tandem Mass Tags (TMTs) labeling approach highlights differences between the shoot proteome of two Arabidopsis thaliana ecotypes, Col‐0 and Ws. Issue 11 (24th May 2021) - Leschevin, Maïté; Marcelo, Paulo; Ismael, Marwa; San‐Clemente, Hélène; Jamet, Elisabeth; Rayon, Catherine; Pageau, Karine
Abstract: Arabidopsis has become a powerful model to study morphogenesis, plant growth, development but also plant response to environmental conditions. Over 1000 Arabidopsis genomes are available and show natural genetic variations. Among them, the main reference accessions Wassilewskija (Ws) and Columbia (Col‐0), originally growing at contrasted altitudes and temperatures, are widely studied, but data contributing to their molecular phenotyping are still scarce. A global quantitative proteomics approach using isobaric stable isotope labeling (Tandem Mass Tags, TMT) was performed on Ws and Col‐0. Plants have been hydroponically grown at 16 h/8 h (light/dark cycle) at 23°C day/19°C night for three weeks. A TMT labeling of the proteins extracted from their shoots has been performed and showed a differential pattern of protein abundance between them. These results have allowed identifying several proteins families possibly involved in the differential responses observed for Ws and Col‐0 during plant development and upon environmental changes. In particular, Ws and Col‐0 mainly differ in photosynthesis, cell wall‐related proteins, plant defense/stress, ROS scavenging enzymes/redox homeostasis and DNA/RNA binding/transcription/translation/protein folding.